Sistem Informasi Penerimaan Siswa Baru Berbasis Web Pada SMK Tinta Emas Indonesia Bekasi - Rahmawati, Annisa; Rofiah, Syahbaniar (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2021)
The development of application technology is used as a means of increasing information in all fields of business, both in the field of education. Admission of new students is the initial stage in the selection process in selecting good students. The problem that occurs at SMK Tinta Emas Indonesia is that there is no information system to record reports in new student admissions. Previously, using bookkeeping and Microsoft excel, it was less effective. The method used is the System Development Life Cycle (SDLC). The results of this study are a web-based new admissions information system. With the admission information system, new students can see announcements and schedules without coming directly to school, and can access reports quickly so that it is effective and does not take much time.